Déficit de democracia intrapartidária e efeitos à capacidade eleitoral passiva: análise dos critérios de distribuição do Fundo Especial de Financiamento de Campanha (FEFC) - Arthur Gandra de Morais (2023)
The aim of this work is to investigate the effects of low intra-party democracy on the passive electoral capacity of affiliates, especially regarding the distribution of campaign resources within the scope of the Special Campaign Financing Fund (FEFC). It is presented as a hypothesis that there are effects and that these are harmful to the passive electoral capacity of the affiliates. In order to demonstrate the hypothesis, the analysis was structured in three analysis vertices: (a) verify the defining elements of passive electoral capacity, investigating its concept and constitutional scope; (b) carry out a survey of the requirements established by the resolutions of political parties for the distribution of FEFC resources; (c) verify the institutional role of the political party within the Brazilian constitutional paradigm and its role as a mediator on the political rights of affiliates, especially electoral capacity passive; (d) evaluate, opposing the normative paradigm and the reflections developed in the previous chapters, the effects of the deficit of intra-party democracy for the effectiveness of the passive electoral capacity of the affiliated to the political parties. The primary source of analysis is the resolutions issued by political parties in the general elections of 2018 and 2022, which determined the criteria for distributing the FEFC to affiliates, with a special focus on the rules for distributing proportional candidacies. In the end, it was found that the FEFC distribution criteria are mostly subjective or discretionary, and the following effects were conditionally diagnosed: (i) insecurity for members; (ii) low material effectiveness of passive electoral capacity; (iii) potential reduction in the access of new cadres or marginalized cadres from the associations to elected positions.